ANALISIS PERBAIKAN DAN BIAYA PERKERASAN JALAN (Studi Kasus Jalan Pati – Gabus) - Bariq Al Salam; Kartono Wibowo; Soedarsono (Jurnal Teknik Sipil dan Arsitektur, 2023)
Highways are one of the important facilities and infrastructure for the achievement of an activity, so a good road pavement design is a must. The existence of highways is very necessary for the need for transportation facilities that can reach remote areas. The increase in traffic volume will result in a decrease in service caused by a decrease in road capacity, in line with the results of the survey/identification conducted, road damage is currently occurring in several areas, especially the Pati-Gabus road section, Pati Regency, which causes considerable losses, especially for road users. , such as congestion, traffic accidents, long travel time and others. Therefore, this research was conducted with the aim of finding alternative pavement designs on the Pati-Gabus road section, and calculating the estimated costs required for pavement repairs. In this study using data obtained through field surveys which are primary data and data collection from the Highways Field of Pati Regency which is secondary data. The results of the study using the Surface Distress Index (SDI) method found that the damage at STA 0+000 to 0+200 was moderately damaged and at STA 0+200 – 1+000 it was lightly damaged and the type of repair was appropriate by looking at the conditions on the Pati road section. -Cork is at STA 0+000 to 1+000 using overlay requires a budget of IDR 2,600,000,000, while at STA 1+000 to STA 2+600 it is heavily damaged and must use rigid pavement requiring budget of IDR 6,341,000,000. Keywords: Road damage, Road repair, Pavement costs